SUGBIDEPA (Smart Urban Green Building Development Planning): Sebagai solusi permasalahan bangunan perkotaan pasca pandemi Covid-19 - Nurfadilah, Reza (Maliki Interdisciplinary Journal, 2024)
The condition of the Covid-19 pandemic has made various lines of life change along with the demands to adapt to prevent prolonged transmission of the virus. One sector that has an impact is the field of architecture specifically in urban areas. The problems in urban areas which are very much compounded by the conditions of the Covid-19 pandemic require all sectors of life to switch to digital, including. The purpose of this article is to convey the ideas of smart cities that are responsive to the conditions of the Covid-19 pandemic. Balanced development between economic growth, social life and environmental protection, so that cities become a place to live not only for the current generation but also for future generations.